Halal certification strategies in minority Muslim regions: A Case study of Doloksanggul, Humbang Hasundutan - Masdinar Sihite; Rahmi Syahriza; Juliana Nasution (LPMP Imperium, 2025)
This study examines strategies for implementing halal certification for MSMEs in Doloksanggul, Humbang Hasundutan Regency, North Sumatra, where Muslims are a minority. Halal certification is vital for catering to Muslim consumers, but its adoption is low—only 0.5% of 288 culinary businesses are certified. Challenges include perceptions of unnecessary certification, limited information, and a lack of awareness about its economic benefits. Despite some government outreach improving awareness, more consistent education and collaboration are needed. The study recommends strategies that consider local cultural dynamics and emphasize enhancing infrastructure, access, and training to boost MSME competitiveness and market reach. Public interest statement: This study is significant for MSMEs in Doloksanggul as it raises awareness about halal certification in areas with minority Muslim populations. It enhances competitiveness, draws in Muslim customers, and offers suggestions for successful government initiatives, ultimately aiding local economic development and community well-being around the Lake Toba tourism area.